Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1097/00002060-200007000-00009
|View full text |Cite
|
Sign up to set email alerts
|

High Intensity Strength Training Improves Strength and Functional Performance After Stroke

Abstract: These results support the concept that strength training is an appropriate intervention to improve the quality of physical function in older community dwelling stroke survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
138
2
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(158 citation statements)
references
References 29 publications
10
138
2
8
Order By: Relevance
“…However, the optimal exercise regimen for improving motor function after stroke remains to be determined. Evidence suggests that progressiveresistance (strength) training of the lower limbs may provide functional benefits [17][18]. Studies of upper-limb resistive exercises after stroke have examined finger strengthening rather than more proximal upper-limb resistance therapy [19][20].…”
Section: Weaknessmentioning
confidence: 99%
“…However, the optimal exercise regimen for improving motor function after stroke remains to be determined. Evidence suggests that progressiveresistance (strength) training of the lower limbs may provide functional benefits [17][18]. Studies of upper-limb resistive exercises after stroke have examined finger strengthening rather than more proximal upper-limb resistance therapy [19][20].…”
Section: Weaknessmentioning
confidence: 99%
“…Weiss et al 4) reported increased leg muscle power, balance and mobility after subjects performed 12 weeks of gradual resistance exercise training using 70% weight of 1 RM of leg muscle. TeixeiraSalmela et al 5) .…”
Section: Discussionmentioning
confidence: 99%
“…However, there are also researchers who have reported that aerobic capacity and mobility can be improved through exercise training even in chronic stroke hemiparetic patients [4][5][6][7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Srivastava et al 6) conducted visual feedback balance training using force plates with 45 chronic stroke patients and reported that the patients' balance and ambulation capabilities improved significantly after the intervention. Weiss et al 7) reported increased leg muscle power, balance, and mobility after 12 weeks of gradual resistance exercise training using 70% weight of 1 RM of leg muscle. A recent study by Bastille and Gill-Body, 8) reported that mobility and balance was improved after chronic stroke patients at more than 9 months after onset performed yoga for 1 hour per 2 times per week for 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are also researchers who have reported that aerobic capacity and balance can be improved through exercise training even in chronic hemiparetic stroke patients [4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%